SOCIAL AND ENVIRONMENTAL RESPONSIBILITY OF INVESTORS RELATED TO INVESTMENT EFFORTS: IMPLICATIONS AND RECONSTRUCTION - Chandra, Ade; Kurniawan, i Gede Agus (Faculty of Law, Universitas Pekalongan, 2024)
Investors' social and environmental responsibility in Indonesia is an important legal and moral obligation, but still faces challenges in its implementation and requires reconstruction and synergy among various stakeholders to achieve sustainable economic development. This research aims to analyze the forms of investors' social and environmental responsibility in investment activities and to formulate the reconstruction of this responsibility in the context of investment in Indonesia. This research uses a normative legal method with statutory and conceptual approaches, analyzing primary and secondary legal materials through literature studies, and conducting qualitative analysis. The results show that the forms of investors' social and environmental responsibility in investment activities encompass economic, social, and environmental aspects, manifested through various programs such as job creation, community empowerment, and environmental conservation efforts. The reconstruction of this responsibility involves strengthening legal sanctions, developing incentive systems, improving monitoring mechanisms, integrating environmental and human rights principles into the CSR legal framework, and enhancing the role of local governments and community participation. The goal of this reconstruction is to ensure that social and environmental responsibility becomes an integral part of corporate business strategy, so that investments can provide sustainable benefits for society and the environment.